Pengembangan Media Pembelajaran Ar-Venture Nusantara pada Materi Keberagaman Budaya Indonesia untuk Siswa Kelas IV di UPT SDN 256 Gresik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to develop AR-Venture Nusantara learning media on Indonesian cultural diversity material for fourth-grade elementary school students and to examine its validity, effectiveness, and practicality. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study was conducted at UPT SDN 256 Gresik with 19 fourth-grade students as research subjects. Data were collected through interviews, media and material expert validation questionnaires, learning achievement tests, and student response questionnaires. The data were analyzed using descriptive quantitative techniques. The results showed that AR-Venture Nusantara media achieved a very valid category, with media expert validation reaching 96.43% and material expert validation reaching 95.31%. The effectiveness of the media was demonstrated by student learning outcomes, where 16 out of 19 students achieved mastery learning with scores ≥75, indicating classical completeness. In addition, the practicality of the media based on student responses reached 86.51% in the very good category. These findings indicate that AR-Venture Nusantara media is valid, effective, and practical for use in IPAS learning, particularly in introducing Indonesian cultural diversity.